National Athletic Trainers' Association position statement: evaluation of dietary supplements for performance nutrition - Buell, J. L.; Franks, R.; Ransone, J.; Powers, M. E.; Laquale, K. M.; Carlson-Phillips, A. (Journal of Athletic Training, 2013)
Objectives: To help athletic trainers promote a "food-first" philosophy to support health and performance, understand federal and sport governing body rules and regulations regarding dietary supplements and banned substances, and become familiar with reliable resources for evaluating the safety, purity, and efficacy of dietary supplements. Background: The dietary supplement industry is poorly regulated and takes in billions of dollars per year. Uneducated athletes need to gain a better understanding of the safety, eligibility, and efficacy concerns associated with choosing to take dietary supplements. The athletic trainer is a valuable athletic team member who can help in the educational process. In many cases, athletic trainers are asked to help evaluate the legality, safety, and efficacy of dietary supplements. For this position statement, our mission is to provide the athletic trainer with the necessary resources for these tasks. Recommendations: Proper nutrition and changes in the athlete's habitual diet should be considered first when improved performance is the goal. Athletes need to understand the level of regulation (or lack thereof) governing the dietary supplement industry at the international, federal, state, and individual sport-participation levels. Athletes should not assume a product is safe simply because it is marketed over the counter. All products athletes are considering using should be evaluated for purity (ie, truth in labeling), safety, and efficacy.